Petroleum geology and sub-source hydrocarbon accumulation of Permian reservoirs in Jinan Sag, eastern Junggar Basin, NW China - Jianzhong LI; Xuan CHEN; Runze YANG; Tong LIN; Fan YANG; Qiang MA; Hongguang GOU; Yanzhao WEI; Lin LIN (Petroleum Exploration and Development, 2023)
According to the latest drilling and the analysis of the burial history, source rock evolution history and hydrocarbon accumulation history, the sub-source hydrocarbon accumulation characteristics of the Permian reservoirs in the Jinan Sag, eastern Junggar Basin, are clarified, and the hydrocarbon accumulation model of these reservoirs is established. The results are obtained in four aspects. First, the main body of the thick salified lake basin source rocks in the Lucaogou Formation has reached the mature stage with abundant resource base. Large-scale reservoirs are developed in the Jingjingzigou, Wutonggou and Lucaogou formations. Vertically, there are multiple sets of good regional seals, the source-reservoir-caprock assemblage is good, and there are three reservoir-forming assemblages: sub-source, intra-source and above-source. Second, dissolution, hydrocarbon charging and pore-preserving effect, and presence of chlorite film effectively increase the sub-source pore space. Oil charging is earlier than the time when the reservoir becomes densified, which improves the efficiency of hydrocarbon accumulation. Third, buoyancy and source-reservoir pressure difference together constitute the driving force of oil charging, and the micro-faults within the formation give the advantage of “source-reservoir lateral docking” under the source rock. Microfractures can be critical channels for efficient seepage and continuous charging of oil in different periods. Fourth, the Jingjingzigou Formation experienced three periods of oil accumulation in the Middle–Late Permian, Middle–Late Jurassic and Late Neogene, with the characteristics of long-distance migration and accumulation in early stage, mixed charging and accumulation in middle stage and short-distance migration and high-position accumulation in late stage. The discovery and theoretical understanding of the Permian reservoirs in the Jinan Sag reveal that the thrust belt has good conditions for forming large reservoirs, and it is promising for exploration. The study results are of guidance and reference significance for oil and gas exploration in the Jinan Sag and other geologically similar areas.